Formalin Test using Extract of Red Chrysanthemum Flower as Indicator into White Tofu and Tempeh (in Ende Traditional Market) - Melania Priska; Veronika P. S. M. Wae; Ludovicus Carvallo; Natalia Peni (CHEMICA: Jurnal Teknik Kimia, 2020)
Formalin in food is very disturbing for the people. Lack of public knowledge about the harmful effects of formaldehyde, the difficulty of distinguishing food that contains and does not contain formaldehyde, lack of knowledge in simply identifying formaldehyde in food is the cause of the increasingly widespread use of formaldehyde in food. This study aims to examine the presence of formalin in white tofu and tempeh circulating in the traditional markets of Ende district by using red chrysanthemum flower extract as a natural indicator. This type of research is an experimental study with descriptive qualitative data analysis techniques. Sampling is done using random sampling techniques. The samples used came from the 3 largest traditional markets in Ende district, namely Wolowona Market, Senggol Market, and Ende Market. From the test results using red chrysanthemum extract showed that the white tofu and tempeh circulating in some traditional markets of Ende district were negative or did not contain formaldehyde. Based on the results of these tests it can be concluded that the red chrysanthemum flower extract can be used as a natural indicator to determine the presence of formalin in food, especially in white tofu and tempeh.